Amelogenin gene influence on enamel defects of cleft lip and palate patients - Fernanda Veronese OLIVEIRA; Thiago José DIONÍSIO; Lucimara Teixeira NEVES; Maria Aparecida Andrade Moreira MACHADO; Carlos Ferreira SANTOS; Thais Marchini OLIVEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to investigate the occurrence of mutations in the amelogenin gene (AMELX) in patients with cleft lip and palate (CLP) and enamel defects (ED). A total of 165 patients were divided into four groups: with CLP and ED (n=46), with CLP and without ED (n = 34), without CLP and with ED (n = 34), and without CLP or ED (n = 51). Genomic DNA was extracted from saliva followed by conducting a Polymerase Chain Reaction and direct DNA sequencing of exons 2 through 7 of AMELX. Mutations were found in 30% (n = 14), 35% (n = 12), 11% (n = 4) and 13% (n = 7) of the subjects from groups 1, 2, 3 and 4, respectively. Thirty seven mutations were detected and distributed throughout exons 2 (1 mutation - 2.7%), 6 (30 mutations - 81.08%) and 7 (6 mutations - 16.22%) of AMELX. No mutations were found in exons 3, 4 or 5. Of the 30 mutations found in exon 6, 43.34% (n = 13), 23.33% (n = 7), 13.33% (n = 4) and 20% (n = 6) were found in groups 1, 2, 3 and 4, respectively. c.261 C > T (rs2106416), a silent mutation, was detected in 26 subjects, and found more significantly (p = 0.003) in patients with CLP (groups 1 and 2 - 23.75%), compared with those without CLP (groups 3 and 4 - 8.23%). In the groups without ED, this silent mutation was also found more significantly (p = 0.032) among subjects with CLP (17.65% in group 2), compared with those without CLP (7.8% in group 4). In conclusion, this study suggested that AMELX may be a candidate gene for cleft lip and palate.